如魚得水？科技女性成功論述之研究 The Discourse of Success by Women Scientists and Technologists - 王雅玄 Ya-Hsuan Wang (National Taiwan Normal University, 2014)
本研究問題意識起於科技性別化社會中，科技女性如何形塑性別氣質、或從其家庭、學校、社會脈絡中獲致其性別化主體。茲以12 位國立綜合大學科技女教授為研究對象，探索高等教育中性別與科技的複雜關係，藉由回顧科技女性個人特質、家庭社經地位與父母教養方式、學校教育、社會文化因素對其科技學習心路歷程的影響，以探討成功論述與性別氣質之關聯。結果發現，科技女性如魚得水的成功論述整合了陽剛個人、平權家庭、女校教育與融入主流社會等四個優勢因素。其最基本的成功論述是以濃厚的科技興趣作為生涯發展的基礎，進而能一路抵抗眾多父權體制下的性別不平等條件。科技女性具有陽剛特質，喜愛閱讀、探索、操作與挑戰；享有平權家庭充足教育資源並受家族科技楷模啟發；在學校受女性科技教師楷模影響並獲益於男女分校與高中文理分流制度；在社會得利於大學聯考分數決定熱門科系並融入主流社會享有母校與同儕的社會資源。本研究呼應Wells（1980）陽剛女性在現代社會中較具發展優勢，此提供科技女性成功論述之參照，然其科技專業發展仍受限於科研領域的父權心態，反映出科技性別化的結構問題。科學教師宜批判察覺社會文化中的性別符碼與規範，實踐性別平等教學，增加女性主體性以利科技領域中的性別平衡發展。 This study is focused on how women scientist and technologists shape their gender subjectivity in the social context of gendered technology. Individual interviews were conducted with 12 women scientists and technologists from 3 national universities in Taiwan. Situating them back to their life experiences of individuality, family, schooling and society, this paper explores their gender role construction and how they articulated the formation of gendered technology. In conclusion, women scientists and technologists simultaneously co-constructed and deconstructed gendered technology and this construction subtly corresponded to changing schooling and societal expectation. The discourse of success by women scientists and technologists was exemplified by gender boundary crossings and self empowerment instigated by personal interest, masculinity, family support, women role models in single-sex schools, and social support from universities. This research corresponded to Wells' (1980) theory that masculine women have developed favorably in modern society. However, gender mobility of elite women has been enabled by patriarchal men, allowing women to survive in social structures with a strict gender boundary.